Organic geochemistry of the lower Pliensbachian Santiurde section (Basque-Cantabrian basin, northern Spain) - Martínez-Braceras, Naroa; Payros, Aitor; Dinarès-Turell, Jaume; Rosales, Idoia; Arostegi, Javier; Silva-Casal, Roi (PANGAEA, 2024)
We present organic geochemistry from the lowermost Pliensbachian organic-rich hemipelagic Santiurde section (Basque-Cantabrian basin, north Iberian palaeomargin, Spain). The Santiurde section studied herein is exposed at exit 144 of motorway A67 (UTM X411431.091 Y4769002.593), approximately 50 km south-west of Santander city. The expanded hemiplegic succession offered a potentially valuable orbitally paced stratigraphic record. An integrated multiproxy study was performed in the 19 beds found between 12.4 and 15.95 m of the lower Pliensbachian succession in order to disentangle what sedimentary processes and environmental factors influenced the formation of the hemipelagic rhytmites. Sampling was mainly carried out in 2019. One sample from the central part of each bed was studied for their mineralogical content, their organic geochemistry, and their elemental composition. Organic carbon and organic nitrogen contents, as well as their isotopic d13Corg and d15Norg values were obtained by combustion of powdered and decarbonated samples in an elemental analyzer Flash EA 1112 (ThermoFinnigan) connected to a DeltaV Advantage mass spectrometer (Thermo Scientific) at the University of A Coruña, Spain.
Keywords: Basque-Cantabria basin; Calcium Carbonate content; colour; inorganic geochemistry; Organic Geochemistry; Pliensbachian; whole-rock mineralogy